Development of a method of continuous improvement of services using the Business Intelligence tools - Svetlana V. Kulikova; Alexander A. Kruglov (Открытое образование (Москва), 2018)
The purpose of the study was to develop a method of continuous improvement of services using the Business Intelligence tools.Materials and methods: the materials are used on the concept of the Deming Cycle, methods and Business Intelligence technologies, Agile methodology and SCRUM.Results: the article considers the problem of continuous improvement of services and offers solutions using methods and technologies of Business Intelligence. In this case, the purpose of this technology is to solve and make the final decision regarding what needs to be improved in the current organization of services. In other words, Business Intelligence helps the product manager to see what is hidden from the “human eye” on the basis of received and processed data. Development of a method based on the concept of the Deming Cycle and Agile methodologies, and SCRUM.The article describes the main stages of development of method based on activity of the enterprise. It is necessary to fully build the Business Intelligence system in the enterprise to identify bottlenecks and justify the need for their elimination and, in general, for continuous improvement of the services. This process is represented in the notation of DFD. The article presents a scheme for the selection of suitable agile methodologies.The proposed concept of the solution of the stated objectives, including methods of identification of problems through Business Intelligence technology, development of the system for troubleshooting and analysis of results of the introduced changes. The technical description of the project is given.Conclusion: following the work of the authors there was formed the concept of the method for the continuous improvement of the services, using the Business Intelligence technology with the specifics of the enterprises, offering SaaS solutions. It was also found that when using this method, the recommended development methodology is SCRUM. The result of this scientific research is the continuous improvement of IT services, using Business Intelligence for enterprises, offering SaaS solutions, which solves the problems, identified in the existing methods of continuous improvement. Proposed method consists of the following steps:– analysis of the current status of the service and identification of bottlenecks;– analysis of possible causes of problems;– formation of requirements to improve services;– development of the part of the system, including troubleshooting; – analysis of the results of the implemented changes;– definition of new measurable criteria and data collection.The developed method was used at the enterprise Ltd “Solomoto”. In the course of practical testing of this method the identified problem of tutorials in SaaS platform Solomoto was eliminated. In addition, they identified several positive effects from the implementation of this method in the enterprise. They include the following:– increase in the quality of requirements’ formation;– improving response to business needs;– reduce costs and negative impact on the implementation of changes;– improving the quality of information on the state of services and the improvement of various metrics; – improving the quality of work of staff;– improving the competitiveness of enterprises through continuous improvement and maintaining the service up to date.